2009
DOI: 10.1016/j.nima.2008.08.017
|View full text |Cite
|
Sign up to set email alerts
|

GEM operation in double-phase xenon

Abstract: a b s t r a c t Operation of Gas Electron Multiplier (GEM) in pure xenon was studied in a double-phase chamber under well-controlled conditions, in terms of temperature, pressure and gas purity. The maximum gain of % 150 was achieved in gas phase at À108 C. Stable operation, during several hours, was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 11 publications
2
24
0
Order By: Relevance
“…It was also observed that the liquid temperature had a significant effect on gain -higher gains could be achieved at lower temperature [304,299], which is consistent with the vapor density considerations. An increase from 165 K to 171 K (from P eq ≈ 1.87 bar to P eq ≈ 2.6 bar) resulted in the decrease of G max from 150 to about 25.…”
Section: Electron Multiplication With Micro-pattern Structuressupporting
confidence: 82%
See 1 more Smart Citation
“…It was also observed that the liquid temperature had a significant effect on gain -higher gains could be achieved at lower temperature [304,299], which is consistent with the vapor density considerations. An increase from 165 K to 171 K (from P eq ≈ 1.87 bar to P eq ≈ 2.6 bar) resulted in the decrease of G max from 150 to about 25.…”
Section: Electron Multiplication With Micro-pattern Structuressupporting
confidence: 82%
“…The GEM foil was placed 3 mm above the liquid surface and operated at vapor pressure of 1.4 bar. The voltage across the GEM (400 V) was well below the multiplication threshold (see Figure 25, right panel [299]). Normalized to 4π, the number of secondary photons produced in the GEM channels was a factor of ∼2 higher than in the uniform field between the liquid surface and the GEM.…”
Section: Optical Readout From Micro-pattern Structuresmentioning
confidence: 98%
“…The proof of principle of this concept was demonstrated: -first in Kr [1], [19]; -then in Ar and Xe [22] and again in Xe [51]; -then in Ar in single electron counting mode with external trigger [52]; -then in Ar with primary scintillation signal readout using CsI photocathode on the first GEM [32];…”
Section: Two-phase Crad With Gem-multiplier Readoutmentioning
confidence: 99%
“…Over the past decade there has been a growing interest in cryogenic detectors with electron avalanching in Gas Electron Multipliers (GEMs) [1], [2], [3], [4], [5], [6] and Thick Gas Electron Multipliers (THGEMs) [7], [8], [9], [10], [11], operating in noble gas media at low temperatures either in a two-phase [1], [3], [4], [5], [6], [8], [9], [10], [11] or gaseous [1], [2], [7] mode. Such detectors could play an important role in rare-event experiments, such as coherent neutrinonucleus scattering [12], dark matter search [13], solar neutrino [14] and large scale neutrino [15] detection, and in gamma-ray imaging techniques such as Positron Emission Tomography (PET) [16], [17] and Compton Telescope [18].…”
Section: Introductionmentioning
confidence: 99%